Modified anti-fog silica sol, preparation and prepared anti-fog paint, anti-fog coating and anti-fog material
The modified anti-fog silica sol was prepared by reaction of Formula 1 and Formula 2, which solved the problems of complex process and insufficient performance of silica sol-based anti-fog coatings in the prior art, and achieved simplified preparation and excellent anti-fog coating performance.
Patent Information
- Application Number
- CN202511193326.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-08-25
- Publication Date
- 2025-11-11
AI Technical Summary
Existing silica sol-based antifog coatings and their coatings have complex compositions and preparation processes, making it difficult to achieve good antifog properties, hardness, and durability simultaneously.
Modified anti-fogging silica sol was prepared by reacting Formula 1 and Formula 2 in a solvent and with a catalyst, and the physicochemical structure was optimized by ring-opening reaction to form an anti-fogging coating.
An anti-fog coating that combines excellent anti-fog performance, hardness, and durability was obtained, simplifying the preparation process and improving interface stability.
Smart Images

Figure CN120923788A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of anti-fog coatings, and more particularly to a silica sol anti-fog coating. Background Technology
[0002] Among the methods for preparing hydrophilic coatings, there are mainly sol-gel method, template method, phase separation method, vapor deposition method and layer-by-layer self-assembly method. Among them, the sol-gel method has the advantages of low equipment cost, easy control of reaction process and good uniformity of coating, which is conducive to the production of large-area hydrophilic coatings. Meanwhile, the dip coating method is simple to operate, suitable for coating on various substrate surfaces, with uniform film formation, low process cost, easy to achieve batch production, and high solution utilization rate, which does not easily lead to waste.
[0003] The coatings used in dip coating are mainly silica sol coatings. Existing technologies have also reported some related techniques. For example, patent document CN106800855A discloses an anti-fogging coating composition, whose components include an organic-inorganic hybrid hydrophilic polymer, a hydrophilic epoxy polymer, a curing agent, a film-forming solvent, and functional additives. Patent document CN111560204A discloses a polycarbonate surface anti-fogging coating and its preparation method, including: 1) preparing an alcohol oligomer reactant monomer and copolymerizing it with acrylic monomers, acrylate monomers, and vinyl silane monomers as a film-forming resin; 2) adding silica sol and hydrolyzing and crosslinking it with the film-forming resin; 3) adding an inorganic metal salt to form an acrylic ionomer. After coating and drying, a self-healing polycarbonate surface anti-fogging coating is obtained. For example, patent document CN113999599A discloses a method for preparing a waterborne polyurethane-silica sol antifog coating. First, a prepolymer synthesized by the acetone method is capped with a polyhydroxy end-capping agent to obtain a hydroxyl-terminated polyurethane prepolymer. Then, it undergoes a chemical bonding reaction with a silane coupling agent containing isocyanate groups to obtain a hydroxyl-terminated organosilicon-polyurethane prepolymer. Next, a neutralization reaction is carried out and the obtained waterborne polyurethane emulsion is emulsified. Finally, it is stirred and mixed with silica sol and a curing agent to obtain a waterborne polyurethane-silica sol antifog coating.
[0004] In summary, existing technologies disclose some silica sol antifog coatings and coating solutions, but most of these solutions require the compounding of numerous antifog active ingredients or complex cross-linking polymerization to improve the antifog performance of the materials. The preparation process of such solutions is complex and difficult to apply industrially. In addition, the stability, hardness and other properties of the antifog coatings formed by such methods need to be further improved. Summary of the Invention
[0005] To address the shortcomings of existing technologies, this invention provides a method for preparing modified anti-fogging silica sol, aiming to prepare a coating that combines excellent hardness, durability, and anti-fogging capabilities based on a simple process.
[0006] The second objective of this invention is to provide a modified anti-fogging silica sol prepared by the aforementioned preparation method.
[0007] A third objective of this invention is to provide an anti-fog coating and an anti-fog coating layer formed from the modified anti-fog silica sol.
[0008] A fourth objective of this invention is to provide an anti-fog material having the aforementioned anti-fog coating.
[0009] Existing silica sol-based antifogging coatings and their preparation methods are complex. Furthermore, it is difficult for antifogging coatings to simultaneously achieve good antifogging properties, hardness, and durability. To address this problem, this invention provides the following improvement:
[0010] A method for preparing a modified anti-fogging silica sol, which is obtained by reacting according to Formula 1 and Formula 2 in a solvent and a catalyst;
[0011] Formula 1
[0012] Formula 2
[0013] In Formula 1, R1 is a C1~C4 alkyl group;
[0014] In Formula 2, R2 is a C1-C4 alkyl group, X is a C1-C6 saturated carbon chain or a heteroatom-hybridized saturated carbon chain, and the heteroatom includes O or N; M is H, Na, K or NH4;
[0015] The catalyst is an acidic or alkaline component.
[0016] This invention innovatively demonstrates that silica sol with anti-fogging properties, durability, and hardness can be prepared through a simple catalytic hydrolysis reaction using Formulas 1 and 2. The preparation method of this invention is simple, and the prepared silica sol exhibits superior interfacial stability, making it suitable for use in anti-fogging coatings to achieve excellent performance.
[0017] In this invention, Formula 2 is obtained by performing a ring-opening reaction using Formulas 3 and 4;
[0018] Formula 3
[0019] Equation 4;
[0020] The selection ranges of R2 and X in Equation 3 are the same as those in Equation 2.
[0021] In this invention, Formula 3 is at least one of Formula 3A and Formula 3B;
[0022] Formula 3A
[0023] Formula 3B.
[0024] In Equations 3A and 3B, the range of R2 is the same as in Equation 3, and n is an integer from 1 to 3.
[0025] Studies have shown that using the preferred formula 3A for the treatment can further optimize the physicochemical structure of the silica sol, which helps to further enhance the anti-fog capability and stability of the obtained anti-fog coating; using formula 3B is more beneficial to the hardness of the anti-fog coating.
[0026] In this invention, when formula 3A is used as a raw material, a product with the structure of formula 2A is obtained through a ring-opening reaction;
[0027] Formula 2A;
[0028] When formula 3B is used as raw material, a product with the structure of formula 2B is obtained through a ring-opening reaction.
[0029] Formula 2B.
[0030] Studies have shown that using the preferred formula 2A for the treatment can further optimize the physicochemical structure of the silica sol, which helps to further enhance the anti-fogging ability and stability of the obtained anti-fogging coating. In addition, although the anti-fogging ability and stability are reduced when using formula 2B for the treatment, the hardness is improved.
[0031] In this invention, the molar ratio of Formula 3 and Formula 4 can be 1:1 to 1.4; more specifically, it can be 1:1.1 to 1.25.
[0032] In this invention, the solvent for the ring-opening reaction can be a hydrophobic solvent, such as DCM, EA, etc.
[0033] In this invention, the ring-opening reaction temperature can be 20~45℃.
[0034] In this invention, the ring-opening reaction time can be 2 to 6 hours.
[0035] In this invention, Formula 1 and Formula 2 can be pre-dispersed in an alcohol-water mixed solvent, and then a catalyst and water can be added to mix and react to obtain the silica sol.
[0036] In this invention, the solvent is an alcohol-water mixed solvent, wherein the alcohol is a C1-C4 alcohol (for example, at least one of methanol, ethanol, and isopropanol). In this invention, the water can be an additional component or introduced from a catalyst solution.
[0037] In this invention, the molar ratio of Formula 1 and Formula 2 is 1 to 5:1; further, it can be 3 to 5:1.
[0038] The amount of water is more than twice the amount of the molar quantity in Formula 2, for example, it can be 4 to 12.
[0039] In this invention, the acidic component in the catalyst includes at least one of glacial acetic acid, hydrochloric acid, sulfuric acid, and nitric acid. Formula 2: The molar ratio of the catalyst is 1:0.05~0.1.
[0040] The alkaline component includes ammonia. Studies have shown that using an alkaline component as a catalyst can further optimize the anti-fogging ability, hardness, and anti-fogging stability of the prepared coating.
[0041] In this invention, when the catalyst is an alkaline component, the pH of the polymerization starting solution can be controlled to be 7.5~8.5.
[0042] The reaction temperature is 20~80℃; it can be further reduced to 20~40℃.
[0043] The reaction time is 12-30 hours, and can be further extended to 15-20 hours.
[0044] In this invention, after polymerization of Formulas 1 and 2, the pH of the resulting silica sol can be adjusted to alkaline conditions (e.g., pH 7.5~8.5). Studies have shown that under preferred conditions, the anti-fogging ability, hardness, and stability of the obtained anti-fogging coating can be further enhanced.
[0045] The present invention also provides a modified anti-fogging silica sol prepared by the above preparation method.
[0046] In this invention, the modified anti-fogging silica sol prepared by the aforementioned preparation method possesses special physicochemical characteristics imparted by the preparation method, and the silica sol prepared by the aforementioned preparation method has excellent stability and surface properties. When used to prepare an anti-fogging coating, an anti-fogging coating that balances excellent anti-fogging characteristics, hardness, and durability can be obtained.
[0047] The present invention also provides an anti-fog coating comprising the modified anti-fog silica sol described in the present invention, and further comprising an initiator.
[0048] In this invention, adding a certain amount of initiator to the coating can further enhance the anti-fogging ability, hardness, and stability of the coating formed by silica sol.
[0049] In this invention, the initiator can be a persulfate, such as ammonium persulfate.
[0050] In this invention, the amount of initiator used is 0.01~0.05 wt% of the weight of the silica sol solid.
[0051] In this invention, leveling agents may also be added to the coating, such as at least one of TIGAR 440 and 450.
[0052] In this invention, the amount of leveling agent used is 0.01~0.05 wt% of the weight of the silica sol solid.
[0053] The present invention also provides an anti-fog coating, which is obtained by drying the anti-fog coating described in the present invention.
[0054] The anti-fog coating of this invention benefits from the innovative use of the special silica sol, which can improve interface stability, surface anti-fog properties, and durability.
[0055] In this invention, the drying temperature is not particularly required, for example it can be 100~130℃; the drying time can be, for example, 1~2h.
[0056] The present invention also provides an anti-fog material, comprising a matrix and an anti-fog coating laminated thereon, wherein the anti-fog coating is the anti-fog coating described in the present invention.
[0057] The substrate described in this invention can be any substrate that requires anti-fogging treatment, such as polyethylene terephthalate, polycarbonate, or glass.
[0058] Beneficial effects
[0059] This invention involves a simple reaction of Formulas 1 and 2 to prepare a silica sol with anti-fogging properties, durability, and hardness. The preparation method of this invention is simple, and the prepared silica sol exhibits superior interfacial stability, making it suitable for use in anti-fogging coatings to achieve excellent performance. Attached Figure Description
[0060] Figure 1 The NMR spectrum of Equation 2A1;
[0061] Figure 2 The water contact angle of the coating prepared in Example 1;
[0062] Figure 3 To demonstrate the anti-fog effect of the coating described in Example 1, the lower half of the left slide is coated with anti-fog liquid, while the right slide is untreated. Detailed Implementation
[0063] The present invention will be further described in detail below with reference to specific examples, but the present invention is not limited thereto.
[0064] Example 1
[0065] Step 1: Weigh out Formula 3A1 (R2 is ethyl of Formula 3A) and Formula 4 in a molar ratio of 1:1.2, dissolve and dilute to a concentration of 25% in dichloromethane, and react at 40°C for 4 hours under nitrogen protection. After removing a small amount of dichloromethane by vacuum distillation, add excess petroleum ether for layer extraction. The petroleum ether layer will become cloudy; wash away any excess unreacted Formula 4. Then, filter the lower layer to obtain a clear, transparent, pale yellow liquid. Remove the solvent by vacuum distillation to obtain Formula 2A1 (R2 is ethyl of Formula 2A and M is H). 1 See H-NMR image Figure 1 , 1 H NMR (400 MHz, CDCl3) δ 7.06 (s, 1H), 6.67 (m = 7.0 Hz, 2H) 3.74 (d, J = 7.0 Hz, 6H), 1.26 (t, J = 7.0 Hz, 10H), 0.02 (s, 3H).
[0066] Step 2: Weigh out Formula 2A1 (1 eqv) and Formula 1A (R1 is ethyl of Formula 1, 4 eqv) and mix them in ethanol. Then add an aqueous acetic acid solution (acetic acid is 0.06 eqv, water is 5 eqv; the volume ratio of alcohol to water is 50:1). React at room temperature for 18±1 h to obtain a hydrophilic silica sol. Then add an initiator (ammonium persulfate, which is 0.02±0.01 wt% of the weight of the silica sol solid) and a leveling agent (Dega 450, which is 0.02±0.01 wt% of the weight of the silica sol solid). Stir at room temperature for 2 h on a magnetic stirrer to obtain a hydrophilic anti-fogging coating.
[0067] Step 3: Apply the hydrophilic coating to a clean substrate (glass that has undergone plasma treatment), bake and cure at 110±10℃ for 1±0.1h, and the thermosetting gel forms a Si-O-Si cross-linked network structure, thereby obtaining the hydrophilic anti-fog coating 1.
[0068] Example 2
[0069] Compared with Example 1, the only difference is that in step one, Formula 3B1 (R2 is ethyl, n is 1, Formula 3B) is used to replace Formula 3A1 in an equal amount to obtain Formula 2B1, which is then used to replace Formula 2A1 in step two for subsequent processing. All other operations and parameters are the same as in Example 1. The final coating is labeled as coating 2.
[0070] Example 3
[0071] Compared with Example 1, the only difference is that in step 2, saturated ammonia water is used to replace glacial acetic acid. That is, saturated ammonia water is used to adjust the pH of the initial system to 8. All other operations and parameters are the same as in Example 1.
[0072] The final hydrophilic anti-fog coating is labeled as coating 3.
[0073] Example 4
[0074] Compared with Example 1, the only difference is that in step 2, no initiator is added; all other operations and parameters are the same as in Example 1. The resulting hydrophilic anti-fog coating is labeled as coating 4.
[0075] Example 5
[0076] Compared with Example 1, the only difference is that in step three, the obtained hydrophilic silica sol is added to potassium carbonate solution to adjust its pH to 7.5-8. All other operations and parameters are the same as in Example 1 to prepare coating 5.
[0077] Example 6
[0078] Compared with Example 1, the only difference is that the glass substrate is not subjected to plasma treatment in step three, while the other operations and parameters are the same as in Example 1 to form coating 6.
[0079] Comparative Example 1
[0080] Compared with Example 1, the only difference is that in step two, no formula 2A1 is added, and all other operations and parameters are the same as in Example 1 to form coating 7.
[0081] Comparative Example 2
[0082] Compared with Example 1, the only difference is that in step one, comparative formula A is used. Replacement 4, with other operations and parameters the same as in Example 1 to make coating 8.
[0083] Comparative Example 3
[0084] Compared with Example 1, the only difference is that step one is not performed. Instead, the same raw materials of formula 3A1 and formula 4 as in Example 1 are used to replace formula 2A1, and step two and subsequent processing are performed directly. The amount of raw materials and other proportions are the same as in Example 1 to make coating 9.
[0085] The glass treated in each case was subjected to abrasion resistance testing: the glass was subjected to 2000 cycles of abrasion resistance under a 500g load, the water contact angle of the glass surface was tested, and the glass was placed on a 60℃ water bath to check for fogging.
[0086] The test results are shown in Table 1:
[0087]
[0088] As can be seen from the data in the table, through Examples 1 and 2, using Formula 3B as raw material, the hydrophilicity is reduced compared to Formula 3A, but the hardness is definitely improved.
[0089] Examples 1 and 3 show that alkaline catalysts catalyze polymerization, which is beneficial to improving the hardness of the coating.
[0090] As shown in Examples 1 and 4, the anti-fogging properties and hardness of the coating are reduced to some extent when no initiator is added.
[0091] As can be seen from Examples 1 and 5, adjusting the silica sol to alkaline conditions not only improves hardness but also provides a better anti-fogging effect.
[0092] As can be seen from Examples 1 and 6, even without pretreatment of the glass substrate, a good anti-fog effect can still be obtained.
[0093] As can be seen from Examples 1-6 and Comparative Examples 1-3, reacting Formula 1 and Formula 2 can unexpectedly improve the anti-fog effect, anti-fog stability, and hardness.
Claims
1. A method for preparing a modified anti-fogging silica sol, characterized in that, It is obtained by reacting Equations 1 and 2 in a solvent and with a catalyst; Formula 1 Formula 2 In Formula 1, R1 is a C1~C4 alkyl group; In Formula 2, R2 is a C1-C4 alkyl group, X is a C1-C6 saturated carbon chain or a heteroatom-hybridized saturated carbon chain, and the heteroatom includes O or N; M is H, Na, K or NH4; The catalyst is an acidic or alkaline component.
2. The preparation method of the modified anti-fogging silica sol as described in claim 1, characterized in that, Equation 2 is obtained by opening the loop using Equations 3 and 4; Formula 3 Equation 4; The selection ranges of R2 and X in Equation 3 are the same as those in Equation 2.
3. The preparation method of the modified anti-fogging silica sol as described in claim 2, characterized in that, Formula 3 is at least one of Formula 3A and Formula 3B; Formula 3A Formula 3B; The range of R2 is the same as in equation 3, where n is an integer from 1 to 3.
4. The preparation method of the modified anti-fogging silica sol as described in claim 1, characterized in that, The acidic components in the catalyst include at least one of glacial acetic acid, hydrochloric acid, sulfuric acid, and nitric acid; The alkaline component includes ammonia.
5. The method for preparing the modified anti-fogging silica sol according to any one of claims 1 to 4, characterized in that, The molar ratio of Equations 1 and 2 is 1 to 5:1; Formula 2: The molar ratio of the catalyst is 1:0.05~0.1; The amount of water is more than twice the molar amount of Formula 2.
6. The method for preparing the modified anti-fogging silica sol according to any one of claims 1 to 4, characterized in that, The reaction process takes place at temperatures ranging from 20 to 80°C. The reaction time is 12-30 hours; Preferably, after the reaction is complete, the pH of the silica sol is adjusted to alkaline conditions.
7. A modified anti-fogging silica sol prepared by the method of claims 1 to 6.
8. An anti-fog coating, characterized in that, The modified antifog silica sol of claim 7 further comprises an initiator.
9. An anti-fog coating, characterized in that, The anti-fog coating as described in claim 8 is obtained by drying.
10. An anti-fog material, comprising a matrix and an anti-fog coating laminated thereon, characterized in that, The anti-fog coating is the anti-fog coating as described in claim 9.
Citation Information
Patent Citations
Antifogging coating layer composition and preparation method and application method thereof
CN106800855A
Self-repairable surface anti-fog coating for polycarbonate and preparation method thereof
CN111560204A
Waterborne polyurethane-silica sol antifogging coating and preparation method and application thereof
CN113999599A